2002
DOI: 10.1038/sj....bjc.6600151...
|View full text |Cite
|
Sign up to set email alerts
|

The molecular pathology of p53 in primitive neuroectodermal tumours of the central nervous system

Abstract: One hundred and one pre-treatment primary central primitive neuroectodermal tumours were analysed for the expression of p53 protein by immunohistochemistry using the monoclonal antibody DO-7. The staining intensity was classified into four groups: strong, medium, weak and negative and strong staining intensity was associated with the poorest survival. DNA sequencing of the p53 gene was performed in 28 cases representing all four staining groups. Mutations were found in only three of the strong staining tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…While extracerebellar PNET were included in several earlier studies, p53 immunoreactivity was not reported separately for these lesions [14,15]. Ho and colleagues documented p53 mutations in 6 of 14 sPNET but did not examine protein expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…While extracerebellar PNET were included in several earlier studies, p53 immunoreactivity was not reported separately for these lesions [14,15]. Ho and colleagues documented p53 mutations in 6 of 14 sPNET but did not examine protein expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 ] Ki-67 and p53 expression was calculated as percentage positivity. [ 6 7 8 ] Patients were followed up after discharge with Glasgow outcome score (GOS) at three and 6 months (as possible). Good recovery was quantified by GOS (4 and 5), fair recovery by GOS (3), and poor recovery with GOS (1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…Although apparently paradoxical, high expression of bona fide tumor suppressor genes, including p16 [18] and p53 [19], have been reported in solid tumor specimens. In the latter study, high levels of wild type p53 were detected in CNS-PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…However, our microarray expression analyses of CNS-PNET specimens revealed a surprisingly high level of FOXO1A expression in one CNS-PNET cell line relative to five other CNS-PNET cell lines and two normal fetal brain specimens. Although over expression of bona fide tumor suppressor genes such as p16 and p53 in cancer specimens has been reported [18,19] the molecular mechanisms by which this occurs and the biological significance of this phenomenon are poorly understood. Since FOXO1A is considered to be a tumor suppressor gene, and little is known about the regulation of FOXO1A mRNA expression levels in mammalian cells, we investigated the molecular mechanisms underlying the high expression of FOXO1A in the PER-453 CNS-PNET cell line.…”
Section: Introductionmentioning
confidence: 99%